MNC Group’s Digital Media Business Expansion in the Perspective of Media Political Economy - Dwinanto Kurniawan; Udi Rusadi (Ikatan Sarjana Komunikasi Indonesia, 2021)
The purpose of this study is to empirically photograph the development of the digital media industry in Indonesia. In particular, this study describes the form of media spatialization carried out by MNC Group using the approach of Vincent Mosco's Media Political Economy Theory. The research approach used is descriptive qualitative with documentation study method to observe and analyse how MNC Group has expanded. The technique of data collection is through documents such as annual reports, publications and other library sources. The results showed that the spatialization carried out strengthened the company's position in the media industry and was able to dominate the market. However, the development of the media industry is not only influenced by technology but also economic and political factors. The power of media on the one hand has a positive impact, but it is also necessary to anticipate impacts that can harm the society when putting economic and political interests above public and social functions. Digital media have a very important role at this time so it needs the involvement of various parties such as the government through regulations to prevent a total media monopoly. In addition, it is also necessary to pay attention to the rights of the community being ignored if the public character is no longer owned by the media.